UNDERSTANDING STUDENT PROFILE SMP IT AL-FITYAN GOWA SCHOOL CLASS IX AT PROBLEM SOLVING VIEWED FROM THE REASONING ABILITY OF MATHEMATICS - Ikrimah Ikrimah (Universitas Negeri Makassar, 2016)
This study is an exploratory study with a qualitative approach that aims to uncover the junior high profile student understanding in solving mathematical problems in terms of mathematical reasoning abilities. The subjects were students of class IX SMP IT Al-Fityan School Gowa consisting of three students with one student has a high mathematical reasoning abilities, one student with mathematical reasoning being, and one student with low mathematical reasoning. Instruments in this study is the researchers themselves as the main instrument that is guided by the mathematical problem solving test, interview, mathematical reasoning ability tests. The study began by determining the subject of research using mathematical reasoning test instruments, and the continuation of TPMM and interviews. Checking the validity of the data using a triangulation of time. The data collection is done by the task analysis and interviews. The data were analyzed by qualitative content analysis technique with a deductive approach that consists of four stages: preparation, organization, presentation and assessment data. The results showed that subjects capable of